Core Theories of Political Communication: Foundational and Freshly Minted. Issue 4 (21st October 2015) - Blumler, Jay G.
Abstract: This article presents and evaluates the essential tenets of a selection of core theories of political communication that leading scholars produced before and after the advent of media abundance, digital communication, and the Internet. From the earlier Foundational Legacy period, a number of theories of media effects, conceptualizations of the politics-media axis, and typologies for comparative analysis of political communication systems are discussed. From the digital era, a number of more freshly minted theories of voice, actors' roles, and holistic and normative perspectives are then considered. In conclusion, the article paints a largely positive picture of the state of political communication theory but also specifies certain needs for further theory development in this highly productive area of communication scholarship.